Diversidade genética de BGMV em linhagens elite de feijoeiro-comum - Bertholdo, Naíze Motta (2021)
Brazil is the main common bean consumer in the world, also being the main producer, whose production supply the intern market. Among the factors that influence the productivity, the wide distribution of Bean golden mosaic virus in common bean fields is very important because it can cause chlorosis, leaf crumpling and stunting, and lead up to 100% yield losses. As a response to that, Embrapa developed, through the RNAi approach, a transgenic common bean line with resistance to the Bean golden mosaic virus. Nonetheless, the presence of a resistance gene can increase the selection pressure over the pathogen, that can mutate and overcome the resistance. Despite being DNA viruses, it is described that in species of Begomovirus, the genus of the BGMV, mutation rates are similar to those of RNA viruses. Nevertheless, until now, BGMV has shown smaller genetic variability compared to other species of the genus. The objective of this work was to characterize BGMV populations that infect different common bean elite lines, transgenic and conventional, in two locations: Brasília and Santo Antônio de Goiás. To that, leaf samples from different elite lines were collected in Value for Cultivation and Use (VCU) trials, searching for differences in viral populations from different sources. We used a strategy widely used on studies related to other living beings: next generation DNA sequencing followed by single nucleotide polymorphisms (SNPs) genotyping. The SNPs obtained were used to carry out genetic diversity analysis. The estimates of the proportion of polymorphic sites and of Nei’s gene diversity revealed a greater genetic diversity in viral populations sampled in transgenic plants. The results suggest that, despite the restriction to the viral replication and, therefore, of smaller viral populations, the necessary conditions to the occurrence of selection pressure are given. In the genetic structure analysis, a significant effect was attributed to localities, as has been widely described in literature.